If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + -5x = -12 Solving -2 + -5x = -12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -5x = -12 + 2 Combine like terms: -2 + 2 = 0 0 + -5x = -12 + 2 -5x = -12 + 2 Combine like terms: -12 + 2 = -10 -5x = -10 Divide each side by '-5'. x = 2 Simplifying x = 2
| -4n+7-3n-2= | | 4x-12.52=3x+12.48 | | -10x+122=282 | | 10=-4m-6m | | 0.6x-2=0.28x+6 | | 23-5-5= | | (3x-5)(x+3)=(3x-5)(-3x-1) | | -9x-45=171 | | 0.4x-4=0.05x+3 | | -47-5x=-137 | | 1=5n-3-1 | | 0.3x-1=0.5x+4 | | 2y-5n= | | 24+8x=-96 | | -4K+3=-13 | | 10x+61=-59 | | 5.25+b=22.75 | | 8x+16=100 | | 40-6x=-116 | | g(x)=1482 | | 0.5x*10=0.15 | | 14n^2/2n^2 | | -5(x-6)=-34+3x | | 3m-m^2=2 | | -18x+102=354 | | 0.6-4=2.6 | | 10=0.10x | | 9x+27=100 | | 10/0.10 | | 8+8m=4+8m+8 | | 8+8m=4+8m+4 | | 3x-2+4=70 |